The role of the behavior analyst on interprofessional mental health teams: opportunities for collaboration and enhancing patient care. Issue 3 (4th May 2022) - Summers, Jane; Busch, Louis; Kako, Milena; Lau, Catherine
ABSTRACT: Patients living with mental illness have needs that span a range of professional disciplines, settings, and service systems. These needs are best addressed through interprofessional collaboration. Behavior analysts can play a valuable role in enhancing patient care as part of the interprofessional mental health team. We provide information about the field of applied behavior analysis and its contribution to the assessment and treatment of patients living with mental health and substance use challenges. We outline how behavior analysts are trained and touch upon the practice of behavior analysis in North America and beyond. We describe collaborative relationships with other mental health professionals and, as an example, review the role of the behavior analyst on interprofessional teams in our mental health and addiction teaching hospital in Canada. We highlight some of the challenges faced by behavior analysts working in the mental health field and offer suggestions to increase their profile and opportunities for collaboration in clinical programs.